2018
DOI: 10.1021/acs.jpcb.8b09398
|View full text |Cite
|
Sign up to set email alerts
|

Direct Demonstration of DNA Compaction Mediated by Divalent Counterions

Abstract: We unambiguously demonstrated DNA attraction and its regulation mediated by divalent cations Mg2+ and Ca2+ by tethering a DNA single chain at various pH solutions. It is found that DNA is compacted when the pH of the solution containing these divalent counterions is decreased below 5. When the pH of the medium is ∼4, DNA is in an unstable transition state, being able to switch between compact and extensible states. We can also regulate the DNA attraction through a cyclic process of DNA compaction and unravelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The requirement of relatively low level of cation binding for DNA condensation indicates that cation binding to the major groove can be a rather sensitive modulator. One example is that Mg 2 + has been reported to compact λ phage DNA when pH is lowered to ∼4 ( 26 ), which can be explained by H + association in the DNA major groove (e.g. the N7 atom of Adenine has a pKa of ∼3.5) giving the extra bit of positive charge.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of relatively low level of cation binding for DNA condensation indicates that cation binding to the major groove can be a rather sensitive modulator. One example is that Mg 2 + has been reported to compact λ phage DNA when pH is lowered to ∼4 ( 26 ), which can be explained by H + association in the DNA major groove (e.g. the N7 atom of Adenine has a pKa of ∼3.5) giving the extra bit of positive charge.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we unambiguously demonstrated DNA attraction and its regulation mediated by divalent cations Mg 2+ and Ca 2+ , by tethering a DNA single chain by lowering the pH of a solution. It has been found that DNA is compacted when the pH of solution containing these divalent counterions is lowered below 5.0 [25]. In the present study, we try to find the critical charge neutralization needed for DNA attraction or compaction.…”
Section: Introductionmentioning
confidence: 96%
“…The interactions between polyelectrolytes and divalent ions are important for diverse biological phenomena. Multivalent ions can mediate attractive interactions between like-charged objects. This is useful to biological organisms, for example, in DNA packing, where divalent and higher-valent cations can induce attractions between monomers, leading to the compaction of DNA molecules. These attractive forces may also generate adverse effects: divalent ions cause polyelectrolyte brushes, which play an important role as lubricants in cartilage tissue, to shrink and aggregate laterally, thereby decreasing their lubricating power. ,, Besides their biological importance, polyelectrolyte solutions and gels are also employed in a wide array of industrial products, ranging from detergents to toothpastes or drilling muds. These are exposed to divalent ions (primarily Mg 2+ and Ca 2+ ) when dissolved in tap water.…”
mentioning
confidence: 99%